(3GWGQ aj GdJfXje h Jbjje GdGOhGJs - (3GQTO aDGO(B, (3GdJejejs ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2010)
(3eONd aj GdGShGb GdeGdjI , caGAI GdShb GdeGdjI , CShGb GdfbO , Shb QCS GdeGd , Shb QCS GdeGd GdGQOfj , CShGb GdGSge GdYGOjI h JbjjegG , JMdjd Sdhc CSYGQ GdGSge , CShGb GdSfOGJ , Jbjje GdSfOGJ , CShGb GdQgf GdYbGQj , CShGb GdNjGQGJ , CShGb GdeSJbHdjGJ GdeGdjI , CShGb eHGOdGJ CSYGQ GdaGFOI (B.s
(3eQGLY U(B.429 (3; edGMb U(B.433s
Keywords: (3GdCShGb GdeGdjIs; (3GdJfXjes; (3QCS GdeGd(B- (3GdCQOfs